Marine bioprocess engineering : proceedings of an International Symposium organized under auspices of the Working Party on Applied Biocatalysis of the European Federation of Biotechnology and the European Society for Marine Biotechnology, Noordwijkerhout, the Netherlands, November 8-11, 1998 - Osinga, R. (Progress in industrial microbiology, 1999)
This book contains full papers of both oral and poster presentations of the international symposium 'Marine Bioprocess Engineering' which was held in Noordwijkerhout, The Netherlands, 1998. The symposium focused on the bioprocessing of marine natural products. Bioprocess engineering has been the key to success in the commercialization of biotechnology, especially with respect to biopharmaceuticals. In marine biotechnology, both new and existing biotechnological techniques are developed an applied to organisms from marine sources. For marine biotechnology, bioprocess engineering represents the link between discovery and commercialization. The diversity of marine life points to a myriad of new bioproducts waiting to be discovered and developed commercially. The volume begins to bridge the gap between the isolation of products from marine organisms in the laboratory and industrial applications by focusing on the bioprocess-engineering aspects. Reviews and recent developments in product discovery, bio-energy production, cultivation of marine organisms, scale up and product recovery are presented. This publication should ensure that the engineering aspects of marine biotechnology will receive further attention in the future. Exploration of new bioproducts from the ocean should be followed up by a sustainable exploitation of these valuable resources.